Typology of Sounding Curves and Lithological 1D Models of Mineral Prospecting and Groundwater Survey within Crystalline Basement Rocks in the East of Cameroon (Central Africa) Using Electrical Resistivity Method and Koefoed Computation Method - Daniel Hervé Gouet; Arsène Meying; Harlin Leonid Ekoro Nkoungou; Stephane Patrick Assembe; Philippe Njandjock Nouck; Théophile Ndougsa Mbarga (International Journal of Geophysics)
Resistivity method using seventy-sixth (976) Schlumberger vertical electrical soundings along forty-one (41) profiles are conducted in the Batouri and Ngoura subdivisions, East region of Cameroon, to investigate the subsurface layering, mineral potential, and groundwater resource characteristics. Results of quantitative and qualitative interpretation of data using Koefoed computation method reveal two to five layers having geometrical and electrical characteristics of geological layer models: topsoil (0.5 m<ep<3 m; 600<ρ<3000 Ω.m), lateritic soils (3<ep<20 m; 1000<ρ<4000 Ω.m); conductive layer (5<ep<110 m; 100<ρ<1000 Ω.m); fractured/weathered granite (20<ep<60 m; 1000/5000<ρ<3000/9000 Ω.m); clayey layer (5<ep<20 m; 600/1500<ρ<2000/3500 (dry) Ω.m); and fresh granites (ρ>4000 Ω.m). From the qualitative interpretation of VES curves, the subsurface layering is depicted by nine (09) types of sounding curves (G, H, A, QH, KH, HK, HA, HKH, and KHK) characterizing the vertical changes and the typology of sounding curves in the East Cameroon crystalline basements. The lithology of the subsurface is dominated (more than 80%) by geoelectrical and lithological 1D models derived by the H, QH, KH, HK, HA, HKH, and KHK curve types. These models are characterized by the presence of conductive layers and fractured/weathered granites derived from tectonic activities of the region. Also, the resistivity method (VES) applied in this study bring information about variation of the resistivity with depth, geological structures, fractures, and rupture zones in the underground until 120 m depth. These abovementioned information reveal proper hydrogeological and mining conditions for an efficient evaluation of the mineral potential and groundwater resources.